Cranioplasty: A Multidisciplinary Approach - Mee, H.; Anwar, F.; Timofeev, I.; Owens, N.; Grieve, K.; Whiting, G.; Alexander, K.; Kendrick, K.; Helmy, A.; Hutchinson, P.; Kolias, A. (Frontiers in Surgery, 2022)
Decompressive craniectomy (DC) is an operation where a large section of the skull is removed to accommodate brain swelling. Patients who survive will usually require subsequent reconstruction of the skull using either their own bone or an artificial prosthesis, known as cranioplasty. Cranioplasty restores skull integrity but can also improve neurological function (1). Standard care following DC consists of the performance of cranioplasty several months later as historically, there was a concern that earlier cranioplasty may increase the risk of infection (2,3). However, recent systematic reviews have challenged this (4,5) and have demonstrated that an early cranioplasty (within three months after DC) may enhance neurological recovery (1,6). However, patients are often transferred to a rehabilitation unit following their acute index admission and before their cranioplasty. A better understanding of the pathophysiological effects of cranioplasty and the relationship of timing and complications would enable more focused patient tailored rehabilitation programs, thus maximizing the benefit following cranioplasty. This may maximise recovery potential, possibly resulting in improved functional and cognitive gains, enhancement of quality of life and potentially reducing longer-term care needs. This narrative review aims to update multi-disciplinary team regarding cranioplasty, including its history, pathophysiological consequences on recovery, complications, and important clinical considerations both in the acute and rehabilitation settings.